Determinants of Financial Performance: The Role of Profitability and Leverage in the Fast-Moving Consumer Goods (FMCG) Industry - Radeva Grahana Putra (CV. Era Digital Nusantara, 2025)
This study aims to analyze the influence of profitability and leverage on the financial performance of PT Indofood Sukses Makmur Tbk during the 2019-2023 period. This research employs a quantitative approach with a census sampling method, utilizing annual financial report data sourced from the Indonesia Stock Exchange (IDX). Data were analyzed using multiple linear regression techniques. The results indicate that, partially, profitability has a positive and significant effect on financial performance, while leverage has a negative and significant effect on financial performance. Simultaneously, both variables significantly influence the company's financial performance with an Adjusted R Square value of 0.997. This indicates that the predictive model in this study possesses exceptionally high explanatory power, where profitability and leverage account for 99.7% of the variance in financial performance. These findings imply that profit optimization and efficient debt structure management are key to maintaining financial performance stability in the food and beverage industry in the post-pandemic era.